Length of Time Exposed to Air Pollution is Related to Blood Oxygen Saturation in Traffic Control Volunteers in Malang - Tri Johan Agus Yuswanto; Bagas Iman Bahreisy (Aloha International Journal of Health Advancement (AIJHA), 2021)
In Malang City, Indonesia, the number of motorized vehicles is increasing from year to year which causes congestion and air pollution. In this case, there are volunteer traffic control assistants (Supeltas), who are suspected of having affected their oxygen saturation. The purpose of this study was to analyze the relationship between the length of time exposed to air pollution with oxygen saturation in the blood of traffic controller assistant volunteers in Malang City. The design of this study was cross-sectional, involving 30 respondents. Data on the length of time worked were collected through interviews, in addition to checking oxygen saturation through blood gas analysis. The results showed that most of the respondents had oxygen saturation less than normal, with 12-18 months of work time, and 3 hours of work per day. Contingency coefficient test results show p-value = 0.000; which means there is a relationship between the length of time exposed to air pollution with oxygen saturation in the blood. Keywords: air pollution; oxygen saturation; traffic control assistant